Student’s access to scientific information resources using pirate open access sci-hub: A gender perspective - Cahyani, Masita Dewi; Winoto, Yunus; Lusiana, Elnovani (Universitas Majalengka, 2024)
Access to scientific information resources needs to be used by many academicians, especially the students. Some of articles are paywall article so scholarly publications cannot all be freely accessed via the internet and there is an information gap. Because of this, many students access information sources through pirate open access called Sci-Hub. This study aims to determine the differences between male and female students in accessing scientific information sources through Sci-Hub open access pirates. This research provides a gender perspective based on the theory of planned behaviour. This research method uses a quantitative approach with a descriptive survey format. The population in this study were students of Padjadjaran University with sampling techniques using non-probability sampling techniques, namely purposive sampling and data processing using SPSS. The results found that the male mean was higher on the attitude towards behaviour and perceived behaviour control variables while the female mean was higher on the subjective norm variable but the mean difference was not significant. The conclusion is that overall there is no difference between male and female students in accessing scientific information sources through pirate open access Sci-Hub.